The impact of anesthesia method on the severity of oxidative stress during coronary artery bypass grafting with cardiopulmonary bypass - O. N. Gerasimenko; O. A. Grebenchikov; Yu. V. Skripkin; O. R. Onischenko; V. V. Likhvantsev; A. M. Ovezov (Вестник анестезиологии и реаниматологии)
The objective: to investigate the impact of anesthesia method on the severity of oxidative stress in patients after coronary artery bypass grafting with cardiopulmonary bypass.Subjects and methods. Patients were randomized (seed 6556 as of 04.01.2016, www.randomization.com) to Volatile Induction and Maintenance Anesthesia (VIMA) with Sevoflurane group (n = 65) and Total Intravenous Anesthesia with Propofol and Fentanyl (TIVA) group (n = 66). The changes in oxidative stress markers in blood plasma were studied: carbonylated proteins, nitrotyrosine, oxidized forms of low-density lipoproteins – oxy-LDL.Results. At the critical stage with 24 hours after the surgery, statistically significant differences in the carbonyls blood levels were found between VIMA with Sevoflurane and TIVA with Propofol groups: 0.88 (0.79–0.96) nmol/mg protein (nmol/mg) in TIVA group vs 0.81 (0.75–0.91) nmol/mg in VIMA group, p = 0.01; and oxy-LDL levels 0.96 ± 0.40 mg/ml vs 0.83 ± 0.33 mg/ml, respectively, p = 0.04. Nitrotyrosine demonstrated no diagnostic value.Conclusion. It has been suggested that sevoflurane possesses antioxidant properties that can be regarded as a positive quality of VIMA in coronary artery bypass grafting with cardiopulmonary bypass.